Consensus guidelines for lumbar puncture in patients with neurological diseases. Issue 1 (18th May 2017) - Engelborghs, Sebastiaan; Niemantsverdriet, Ellis; Struyfs, Hanne; Blennow, Kaj; Brouns, Raf; Comabella, Manuel; Dujmovic, Irena; van der Flier, Wiesje; Frölich, Lutz; Galimberti, Daniela; Gnanapavan, Sharmilee; Hemmer, Bernhard; et al.
Abstract: Introduction: Cerebrospinal fluid collection by lumbar puncture (LP) is performed in the diagnostic workup of several neurological brain diseases. Reluctance to perform the procedure is among others due to a lack of standards and guidelines to minimize the risk of complications, such as post‐LP headache or back pain. Methods: We provide consensus guidelines for the LP procedure to minimize the risk of complications. The recommendations are based on (1) data from a large multicenter LP feasibility study (evidence level II‐2), (2) systematic literature review on LP needle characteristics and post‐LP complications (evidence level II‐2), (3) discussion of best practice within the Joint Programme Neurodegenerative Disease Research Biomarkers for Alzheimer's disease and Parkinson's Disease and Biomarkers for Multiple Sclerosis consortia (evidence level III). Results: Our consensus guidelines address contraindications, as well as patient‐related and procedure‐related risk factors that can influence the development of post‐LP complications. Discussion: When an LP is performed correctly, the procedure is well tolerated and accepted with a low complication rate.